The democrats must lead the case for a progressive democratic party (Westview Press, 1992)
All over the world, political parties are being born and political pluralism is being fostered. Ironically, here in the United States the parties are blurring together ideologically, and the political process is suffering: One of the messages of this book is that a vital two-party system is essential to America's political health. The last thing this country needs, the authors argue, is two Republican parties. At this critical moment in history, the Democratic party has the opportunity to offer the nation a real political choice, a sense of direction, and a program to address the needs of Americans in a changing world. It is time, they say, for a change--a change that only the Democrats can provide. As recounted here, a generation of Republican administrations have had their chance. The results have not been happy: deepening social divisions, heightened inequalities in income distributions, a decaying educational system, environmental exploitation, an insensitivity to the concerns of the less powerful, the largest public debt in history, and a foreign policy based on force. Recurring constitutional crises have also erupted, as epitomized by the Iran-Contra affair. The record is a sorry one. Alternatives exist and the best ones rest with the Democratic party. The Democrats must lead. It is their responsibility to offer a new vision of the future and the means for achieving it; a program that is compassionate, just, and inclusive of all. Challenging and thought-provoking, these essays should help reshape political thinking during a critical period in the nation's history. Their objective is a society that represents and responds to human needs, and the authors indicate the way to achieve these goals through an invigorated, forward-looking Democratic party.